PENERAPAN PENDEKATAN COMPUTATIONAL THINKING UNTUK MENINGKATKAN KEMAMPUAN PROBLEM SOLVING PADA MATERI GEOMETRI PESERTA DIDIK KELAS IV MI - Intan Kuswari, Retno; Shofiyah, Siti; Nafsi, Filzatun (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
This study focuses on enhancing the Problem Solving skills of fourth-grade students at MI Tarbiyatussibyan for the 2025/2026 academic year through the integration of a Computational Thinking approach in Geometry. The research employed a qualitative Classroom Action Research (CAR) design conducted in two cycles, with each cycle encompassing planning, implementation, evaluation, and reflection. The instructional process incorporated Computational Thinking phases, specifically tinkering, creating, debugging, persevering, and collaborating. Success indicators were assessed based on George Polya’s four steps of problem-solving. Data were collected through tests, interviews, and observations, and subsequently analyzed using qualitative descriptive methods. The results demonstrated positive progress: in Cycle I, two aspects met the average standard, increasing to four aspects in Cycle II. Consequently, it can be concluded that the Computational Thinking approach is effective in enhancing students' Problem Solving abilities. Keywords: Computational Thinking, Problem Solving, Geometry